Vloga proaktivne in odzivne tržne naravnanosti za razvoj inovacijskih virov - Milfelner, Borut (Naše gospodarstvo, 2009)
The present contribution discusses the role and importance of two aspects of market orientation, responsive and proactive. In this empirical study, market orientation is set as an important predecessor of innovation resources. The study was conducted using a sample of 3000 firms in Slovenia with more than 20 employees. Results indicate that proactive and responsive market orientation has an important influence on innovativeness, while the capacity to innovate is mainly influenced by proactive market orientation, which seems to be a key resource for organizational competitive advantage development.
Keywords: marketing; trženje; inovativnost; inovativno poslovanje; inovativno mišljenje; poslovna uspešnost; konkurenčnost